DNA interstrand crosslink repair during G1 involves nucleotide excision repair and DNA polymerase zeta. - Sarkar, S; Davies, A; Ulrich, H; McHugh, P (2006)
The repair mechanisms acting on DNA interstrand crosslinks (ICLs) in eukaryotes are poorly understood. Here, we provide evidence for a pathway of ICL processing that uses components from both nucleotide excision repair (NER) and translesion synthesis (TLS) and predominates during the G1 phase of the yeast cell cycle. Our results suggest that repair is initiated by the NER apparatus and is followed by a thwarted attempt at gap-filling by the replicative Polymerase delta, which likely stalls at the site of the remaining crosslinked oligonucleotide. This in turn leads to ubiquitination of PCNA and recruitment of the damage-tolerant Polymerase zeta that can perform TLS. The ICL repair factor Pso2 acts downstream of the incision step and is not required for Polymerase zeta activation. We show that this combination of NER and TLS is the only pathway of ICL repair available to the cell in G1 phase and is essential for viability in the presence of DNA crosslinks.